The Effect of Good Corporate Governance on Company Value with Financial Performance as an Intervening Variable in State-Owned Companies Listed on the Indonesia Stock Exchange 2016-2018: Pengaruh Good Corporate Governance Terhadap Nilai Perusahaan Dengan Kinerja Keuangan Sebagai Variabel Intervening Pada Perusahaan Bumn Yang Terdaftar Di Bursa Efek Indonesia Tahun 2016-2018 - Nikmah Nurhidayah; Eny Maryanti (Universitas Muhammadiyah Sidoarjo, 2021)
The purpose of this study is to prove and analyze the effect of good corporate governance as measured by three indicators, namely independent commissioners. the board of directors and the audit committee on the value of the company through financial performance. This study uses state-owned companies listed on the Indonesia Stock Exchange in 2016-2018 as the population with a total number of 60 companies. The sample was selected using purposive sampling method. This study used a quantitative approach and the research data was tested using Partial Least Square (PLS) data processing. From the calculation results, it is concluded that independent commissioners and audit committees have an influence on firm value. Meanwhile, the board of directors has no influence on firm value. Other results show that independent commissioners and audit committees have no effect on firm value through financial performance. While the board of directors affects the value of the company through financial performance.